Animal nutrition - McDonald, Peter , 1926- (Pearson, 2011)
Animal Nutrition is a core text for undergraduates in Animal Science, Veterinary Science, Agriculture, Biology and Biochemistry studying this subject. It also provides a standard reference text for agricultural advisers, animal nutritionists and manufacturers of animal feeds.-- COVER